PROX1 is a transcriptional regulator of MMP14 - Silvia Gramolelli (Nature Portfolio, 2018)
Abstract The transcription factor PROX1 is essential for development and cell fate specification. Its function in cancer is context-dependent since PROX1 has been shown to play both oncogenic and tumour suppressive roles. Here, we show that PROX1 suppresses the transcription of MMP14, a metalloprotease involved in angiogenesis and cancer invasion, by binding and suppressing the activity of MMP14 promoter. Prox1 deletion in murine dermal lymphatic vessels in vivo and in human LECs increased MMP14 expression. In a hepatocellular carcinoma cell line expressing high endogenous levels of PROX1, its silencing increased both MMP14 expression and MMP14-dependent invasion in 3D. Moreover, PROX1 ectopic expression reduced the MMP14-dependent 3D invasiveness of breast cancer cells and angiogenic sprouting of blood endothelial cells in conjunction with MMP14 suppression. Our study uncovers a new transcriptional regulatory mechanism of cancer cell invasion and endothelial cell specification.